Herpes simplex virus type 1 in subgingival plaque and periodontal diseases. Meta‐analysis of observational studies. (3rd January 2022) - Arduino, Paolo G.; Cabras, Marco; Lodi, Giovanni; Petti, Stefano
Abstract: Background and objectives: This meta‐analysis of observational studies (PROSPERO registration number CRD42021236054) sought to investigate strength and generalizability of the association of herpes simplex virus type 1 (HSV‐1) in subjects with plaque‐induced gingivitis and periodontitis, since the data from literature are contrasting. Material and methods: Case–control and cross‐sectional studies, investigating HSV‐1 in subgingival plaque/crevicular fluid and periodontal status, were searched through MEDLINE via PubMed, Scopus, Web of Science and Google Scholar. From each study the crude odds ratio (OR) with 95% confidence interval (95CI) was extracted, and the pooled OR was assessed for periodontitis, chronic and aggressive, and gingivitis. The meta‐analytic method was chosen based on the level of heterogeneity. The generalizability of results, determined by the meta‐analysis bias, was investigated through secondary analyses including sensitivity analyses for study quality, publication bias, and study inclusion, and subgroup analyses for quality of scientific journals that published the primary studies, world Region, subgingival plaque sampling method and study design. Results: Twelve studies were included (738 cases, 551 controls). The pooled ORs were 4.4 (95CI, 1.9–10.2) for any periodontitis; specifically, 2.8 (95CI, 1.0–8.3) for chronic periodontitis, 11.8 (95CI, 5.4–25.8) for aggressive periodontitis and 4.8 (95CI, 2.1–11.0) for gingivitis. These estimates were statistically significant, excluding for chronic periodontitis, resulting marginally significant ( p  = .05). Secondary analyses on any and aggressive periodontitis, and, partly, chronic periodontitis corroborated the results, while the material was insufficient for secondary analyses on gingivitis. Conclusions: The results obtained indicated that HSV‐1 is associated with periodontitis, while data about gingivitis are inconclusive. HSV‐1 investigation in subgingival plaque could help assess periodontitis risk and severity and, if causal association were confirmed, could contribute to its control.